Analisis kualitas pelayanan (service quality) terhadap kepuasan konsumen pada rumah makan sop ayam Pak Min Klaten di Malang - Yansah, Riyan Afri; Hartono, Budi; Hariyono, M. B. (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2013)
The objective of this research was to identify consumer behavior and to analyze factors that influenced consumer satisfaction in purchasing products of sop ayam Pak Min Klaten in Malang. The research was conducted from December 2012 to January 2013. One hundred and fifty customers were chosen as respondents by accidental sampling method. Data were analyzed by multiple regression analysis. The study found that there were significant influences between tangible, reliability, responsiveness, assurance and empathy on customer satisfaction. The study concluded that tangible, reliability and empathy influenced dominantly customers’ satisfaction. Keywords: tangible, reliability, responsiveness, assurance, empathy, customer satisfaction